Structure-based design of a hyperthermostable AgUricase for hyperuricemia and gout therapy - Shi Yi; Wang Ting; Zhou X. Edward; Liu Qiu-feng; Jiang Yi; Xu H. Eric (Acta Pharmacologica Sinica, 2019)
Arthrobacter globiformis Uricase (AgUricase) is a homotetrameric uricase with the potential for therapeutic use in treating hyperuricemia-related diseases. To achieve sufﬁcient therapeutic effects, it is essential for this enzyme to have high thermostability and long half-life in physiological condition. To improve the thermostability of this enzyme, we introduced a series of cysteine pair mutations into the AgUricase subunits based on its structural model and studied the thermostability of the mutant enzymes with introduced disulﬁde bridges. Two intersubunit cysteine pair mutations, K12C–E286C and S296C–S296C, were found to markedly increase the melting temperatures of the corresponding mutant enzymes compared with WT AgUricase. The crystal structure of the K12C–E286C mutant at 1.99 Å resolution conﬁrmed the formation of a distinct disulﬁde bond between the two subunits in the dimer. Structural analysis and biochemical data revealed that the C-terminal loop of AgUricase was ﬂexible, and its interaction with neighboring subunits was required for the stability of the enzyme. We introduced an additional intersubunit K244C–C302 disulﬁde bond based on the crystal structure of the K12C–E286C mutant and conﬁrmed that this additional disulﬁde bond further stabilized the ﬂexible C-terminal loop and improved the thermostability of the enzyme. Disulﬁde cross-linking also protected AgUricase from protease digestion. Our studies suggest that the introduction of disulﬁde bonds into proteins is a potential strategy for enhancing the thermostability of multimeric proteins for medical applications.